EXPLORING RELIGIOUS MODERATION FROM THE PERSPECTIVE OF GENDER AND GENERATION IN YUSUF AZEEM IS NOT A HERO (2021) - Waode Surya Darmadali, M.Hum; Jihan Fitrah Haris Kuruseng; Anas, Andi Iqram (UIN Alauddin Makassar, 2025)
This study examines religious moderation in the novel Yusuf Azeem Is Not a Hero (2021) through the perspectives of gender and generation, analyzing how values such as understanding differences, controlling emotions, rejecting violence, and promoting social harmony are transmitted in Muslim families in a predominantly non-Muslim environment. Data were collected from selected quotations and narrative sections in the novel that describe the characters' responses to prejudice and discrimination with an understanding of religious moderation by Lukman Hakim and Boehnke's theory of intergenerational transmission of values. Using qualitative descriptive methods, the researcher identified religious moderation in Muslim families. The findings of this study are that Yusuf's father (Abba) applies religious moderation through emotional control, fighting evil with kindness and interfaith engagement, while Yusuf's mother (Amma) leads public advocacy in promoting true Islam, and the protagonist Yusuf represents the values of both his parents in his peaceful response to Islamophobia in his school and home environments, showing that religious moderation is a behavior that can be passed down and shapes Muslim identity and resilience.